Built-in electric field enhancement/retardation on intermixing - Xu, C. D. (2010)
The built-in electric field may impose a drift on charged point defects and may thus enhance or retard the intermixing during annealing. Electric field is built-in near the surface due to the pinning of surface Fermi level after argon plasma treatment on InP surfaces of InP/InGaAs quantum well samples. Subsequent annealing leads to different intermixing results due to the different field directions on InP cap layers in different doping types. Experiments also showed different influences of the built-in field on the two sublattices largely due to different charge numbers of point defects on the respective sublattices.